Berm breakwaters, tailor-made size graded structures - Sigurdarson, S. (author); Viggosson, G. (author); Benediktsson, S. (author); Smarason, O.B. (author) (KVIV, 1996)
This paper describes the 13 year experience of design and construction of rubble mound berm breakwaters in Iceland. Over twenty berm structures have been constructed since 1983. All berm breakwaters in Iceland have been constructed by local contractors who have developed considerable experience in this type of work. The paper describes the design philosophy of berm breakwaters which aims at optimizing the structure with respect to wave load and possible yield from an armour stone quarry. The estimated yield from an armour stone quarry is used as an integrated part of the design process in an attempt to optimize the utilization of the quarry. All size grades from the quarry are used and in many cases a 100% utilization is achieved. Breakwaters and shore protection in Iceland are mostly constructed from locally quarried rock. Rock quality is variable depending on rock type. jointing, density and degree of alteration. Porphyritic basalt and gabbro have excellent to good quality, whereas other basalts are generally good to poor. Fracture measurements are used to forecast quarry yield for rubble mound structures and are usually very close to the results of blasting. A quality assurance programme has been developed to guarantee that rocks intended for breakwaters are up to the required standard in each case. The Icelandic Harbour Authority has developed a variant of the original berm concept with all the advantages of the berm concept although the structure is much more stable. This variant can be described as a "tailor-made size graded berm". It allows the use of even smaller stones inside the berm. than in berm breakwaters of only one or two stone classes and as a consequence larger stone classes can be used to reinforce the structure. In many cases this design approach leads to a less expensive structure than the original berm concept. although the structure is much more stable. Berm Breakwaters